Harmonic memory signals in the human cerebral cortex induced by semantic relatedness of words - Yasuki Noguchi (npj Science of Learning, 2024)
Abstract When we memorize multiple words simultaneously, semantic relatedness among those words assists memory. For example, the information about “apple”, “banana,” and “orange” will be connected via a common concept of “fruits” and become easy to retain and recall. Neural mechanisms underlying this semantic integration in verbal working memory remain unclear. Here I used electroencephalography (EEG) and investigated neural signals when healthy human participants memorized five nouns semantically related (Sem trial) or not (NonSem trial). The regularity of oscillatory signals (8–30 Hz) during the retention period was found to be lower in NonSem than Sem trials, indicating that memorizing words unrelated to each other induced a non-harmonic (irregular) waveform in the temporal cortex. These results suggest that (i) semantic features of a word are retained as a set of neural oscillations at specific frequencies and (ii) memorizing words sharing a common semantic feature produces harmonic brain responses through a resonance or integration (sharing) of the oscillatory signals.